2013
DOI: 10.1002/jbm.b.32994
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and cytotoxicity testing of acrylic bone cement embedded with microencapsulated 2‐octyl cyanoacrylate

Abstract: The water-reactive tissue adhesive 2-octyl cyanoacrylate (OCA) was microencapsulated in polyurethane shells and incorporated into Palacos R bone cement. The tensile and compressive properties of the composite material were investigated in accordance with commercial standards, and fracture toughness of the capsule-embedded bone cement was measured using the tapered double-cantilever beam geometry. Viability and proliferation of MG63 human osteosarcoma cells after culture with extracts from Palacos R bone cement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 61 publications
3
11
0
Order By: Relevance
“…Table 1 lists the average diameters and shell thicknesses of the capsules prepared in these studies. These results were consistent with previously reported data on capsule fabrication [10, 13]. …”
Section: Resultssupporting
confidence: 94%
See 4 more Smart Citations
“…Table 1 lists the average diameters and shell thicknesses of the capsules prepared in these studies. These results were consistent with previously reported data on capsule fabrication [10, 13]. …”
Section: Resultssupporting
confidence: 94%
“…This observation was expected as we already reported that 5wt% capsular content was the upper limit for acceptable PMMA bone cement compression, tension, and fracture toughness properties [13]. Interestingly, the bending modulus E remained nearly constant regardless of capsule content in OCA and No OCA samples (Figure 2B).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations